Proyecto de vida a partir de un embarazo precoz: Estudio de caso en mujeres adultas desde una perspectiva comunicacional. - Quiroga Catota, Jessica Paola (2018)
A teenage pregnancy implies that a girl will become a mother to another girl. In view of this, a study was conducted in girls who had a teenage pregnancy. The essence of the project focuses on the collection of the past experience, because the analysis units were currently adult women with experience of an early pregnancy. The general objective of the research was to analyze how women in the parish of Toacazo, currently adults, built their life project from their teenage pregnancy. It was identified that changes in the course of life of a teenager from an early pregnancy can be visualized in adulthood. Therefore, the researcher investigated the senses of life that women of the Toacazo parish, currently adults, acquired from their teenage pregnancy and influenced the construction of their life project. The methodology used was non-experimental design, transversal descriptive, from a qualitative approach, therefore is not representative statistically. Taking thus, eight adult women whose age range was between 25-35 years and their children did not exceed the age of 19 years. The researcher worked with the research technique of "case study" and the research instruments used to access the discourse of the participants was the individual interview with their respective questionnaire. It is concluded that none of the women who interviewed fulfilled the project of life they had planned in adolescence. Based on the results, it can be indicated that the main element that affected the construction of a new life project was the pregnancy, therefore, they all had to leave their studies and look after of their children.